Host‐induced gene silencing of BcTOR in Botrytis cinerea enhances plant resistance to grey mould. (17th October 2019) - Xiong, Fangjie; Liu, Mei; Zhuo, Fengping; Yin, Huan; Deng, Kexuan; Feng, Shun; Liu, Yudong; Luo, Xiumei; Feng, Li; Zhang, Shumin; Li, Zhengguo; Ren, Maozhi
Summary: Botrytis cinerea is the causal agent of grey mould for more than 200 plant species, including economically important vegetables, fruits and crops, which leads to economic losses worldwide. Target of rapamycin (TOR) acts a master regulator to control cell growth and proliferation by integrating nutrient, energy and growth factors in eukaryotic species, but little is known about whether TOR can function as a practicable target in the control of plant fungal pathogens. Here, we characterize TOR signalling of B. cinerea in the regulation of growth and pathogenicity as well as its potential value in genetic engineering for crop protection by bioinformatics analysis, pharmacological assays, biochemistry and genetics approaches. The results show that conserved TOR signalling occurs, and a functional FK506‐binding protein 12 kD (FKBP12) mediates the interaction between rapamycin and B. cinerea TOR (BcTOR). RNA sequencing (RNA‐Seq) analysis revealed that BcTOR displayed conserved functions, particularly in controlling growth and metabolism. Furthermore, pathogenicity assay showed that BcTOR inhibition efficiently reduces the infection of B. cinerea in plant leaves of Arabidopsis and potato or tomato fruits. Additionally, transgenic plants expressing double‐stranded RNA of BcTOR through the host‐induced gene silencing method could produce abundant small RNAs targeting BcTOR, and significantly block the occurrence of grey mould in potato and tomato. Taken together, our results suggest that BcTOR is an efficient target for genetic engineering in control of grey mould, and also a potential and promising target applied in the biocontrol of plant fungal pathogens.